Current market trends in anterior ocular inflammatory disease landscape. Issue 5 (October 2019) - Khan, Rubba Shoukat; Rizvi, Salman; Syed, Basharut A.; Bielory, Leonard
Abstract : Purpose of review: In the US anterior ocular inflammatory disease (AOID) composed of the spectrum of ocular allergies, different forms of infectious conjunctivitis, and dry eye diseases, affects over 40% of the population. This review evaluates the current economic costs for AOID associated pharmacotherapies. Recent findings: In recent years, with improved understanding in pathophysiology of the AOID, providing novel targets for pharmacotherapy, have led to considerable improvements in outcomes for patients. Despite these advances, there continues to be a need for interventions that inhibit key inflammatory mediators or pathways in the ophthalmic space. In 2018, AOID drugs market represents ∼40% of the costs for the total ophthalmic drugs: dry eye (43%), antiinfectives (15%), antiallergics (13%), and antiinflammatory agents (29%). With increasing treatment costs, the need for improved, cost-effective modalities persists along with treatment algorithms to derive optimal benefits for patients. Summary: There has been a dramatic increase in the economic burden of AOID with the annual expenditure for the prescription drugs approaching close to $11 billion in 2018. With increasing prevalence of ocular disease, further investment is required to provide more effective treatment options and deliver improved public health and economic outcomes.